Ophthalmic Use of Targeted Biologics in the Management of Intraocular Diseases: Current and Emerging Therapies - Yuan Zong; Miki Miyagaki; Mingming Yang; Jing Zhang; Yaru Zou; Kyoko Ohno-Matsui; Koju Kamoi (Antibodies)
Background: Monoclonal antibodies (mAbs) have demonstrated substantial potential in the treatment of intraocular diseases. This review aimed to comprehensively evaluate the applications, efficacy, and safety of mAbs in the management of intraocular conditions. Methods: A comprehensive literature search was conducted in major medical databases through July 2024. Relevant studies on monoclonal antibodies for intraocular diseases were included. Two independent researchers screened the literature, extracted data, and assessed study quality. Cost-effectiveness analyses were also reviewed. Results: Anti-vascular endothelial growth factor (VEGF) antibodies, such as bevacizumab, ranibizumab, and aflibercept, showed significant therapeutic effects in neovascular age-related macular degeneration (NVAMD), diabetic macular edema (DME), and retinal vein occlusion (RVO). Tumor necrosis factor-alpha (TNF-α) inhibitors demonstrated promising results in treating noninfectious uveitis. Complement system-targeted therapies like pegcetacoplan offered new options for geographic atrophy. Anti-VEGF antibodies showed potential in managing retinopathy of prematurity (ROP). However, challenges persist, including high costs, potential drug resistance, and limited long-term safety data in certain scenarios. Conclusions: Monoclonal antibodies are vital for treating intraocular diseases, but continuous innovation and rigorous clinical evaluation are essential. Future research should focus on developing novel delivery systems, exploring combination therapies, conducting long-term follow-up studies, and investigating personalized treatment strategies to provide safer, more effective, and cost-effective therapeutic solutions.